Postnatal light alters hypothalamic‐pituitary‐adrenal axis function and induces a depressive‐like phenotype in adult mice. (18th September 2016) - Coleman, Georgia; Gigg, John; Canal, Maria Mercè
Abstract: The postnatal light environment that a mouse experiences during the critical first three postnatal weeks has long‐term effects on both its circadian rhythm output and clock gene expression. Furthermore, data from our lab suggest that postnatal light may also impact the hypothalamic‐pituitary‐adrenal (HPA) axis, which is a key regulator of stress. To test the effect of postnatal light exposure on adult stress responses and circadian rhythmicity, we raised mice under either 24‐h light– dark cycles (LD), constant light (LL) or constant dark (DD) during the first three postnatal weeks. After weaning we then exposed all animals to LD cycles (basal conditions), followed by LL (stressed conditions) environments. We examined brain neuropeptide and glucocorticoid receptor (GR) expression, plasma corticosterone concentration rhythm and body temperature rhythm, together with depression‐ and anxiety‐related behaviour. Results showed that LL‐ and DD‐raised mice exhibited decreased GR expression in the hippocampus, increased plasma corticosterone concentration at the onset of the dark phase and a depressive phenotype when exposed to LD cycles later in life. Furthermore, LL‐raised mice showed increased corticotrophin‐releasing hormone mRNA expression in the paraventricular nucleus of the hypothalamus. When exposed to LL as adults, LL‐raised mice showed a significant circadian rhythm of plasma corticosterone concentration, together with a shorter period and stronger circadian rhythm of body temperature compared to DD‐raised mice. Taken together, these data suggest that altered postnatal light environments have long‐term effects on the HPA axis and the circadian system, which can lead to altered stress responses and a depressive phenotype in adulthood. Abstract : Postnatal light experience has imprinting effects on clock genes and circadian behaviour. In addition to these, here we demonstrate that early light environment can also shape the development of the HPA axis, which can lead to altered stress responses and a depressive phenotype in adulthood.